1963
DOI: 10.1017/s0021859600013800
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of embryo size and endosperm size in causing the effects associated with seed size in wheat

Abstract: 1. The growth of wheat plants at two depths of planting, from seed in which embryo size and endosperm size were varied independently was studied.2. Embryo size was shown to have a negligible effect on growth, whilst endosperm size had a considerable effect; the influence of neither embryosize nor endosperm size appeared to be in any way modified by depth of planting. It is suggested that the relationship between seed size and plant size is governed by the amount of reserve material present in the seed.3. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

1970
1970
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 12 publications
4
39
0
2
Order By: Relevance
“…Taylor and Ten Broeck (1988) demonstrated that the amount of seedling emergence force expended increased linearly as seed size increased for an array of small-to large-seeded vegetable crops. However, an inverse relation existed between the capacity of seeds to use reserve materials and small-sized seeds were more efficient in using this reserve materials than large ones (Bremner et al 1963, Taylor & Ten Broeck 1988. In our experiment the small seeds showed higher early germination than large seeds (Table 1) which can be explained by the rapid imbibition of moisture which accelerate both physiological and chemical process of germination.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor and Ten Broeck (1988) demonstrated that the amount of seedling emergence force expended increased linearly as seed size increased for an array of small-to large-seeded vegetable crops. However, an inverse relation existed between the capacity of seeds to use reserve materials and small-sized seeds were more efficient in using this reserve materials than large ones (Bremner et al 1963, Taylor & Ten Broeck 1988. In our experiment the small seeds showed higher early germination than large seeds (Table 1) which can be explained by the rapid imbibition of moisture which accelerate both physiological and chemical process of germination.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in wheat, maize and other cereal crop plants, the endosperm constitutes more than 80% of total seed weight. In such plants, the size, capacity for dormancy, viability, durability and fitness of seeds is determined by the size of the endosperm and not that of the embryo (Martin, 1946;Bremner et al, 1963; also see Garcia, 2003Garcia, , 2005. In contrast, in younger dicot families, such as cucurbits and orchids, the endosperm is reduced to a couple of layers of cells.…”
Section: Endospermmentioning
confidence: 99%
“…Seeds collected from delayed sowing had more robust seedlings, which is also supported by their bigger crown diameter and higher seedling dry weight. Seedling growth is associated with seed size (Austin and Condon, 1967;Bremmer et al, 1963). The linear relationship between seedling dry weight with root (R 2 =O.9565) or shoot (R 2 =O.7860), dry weight was quite positive (Fig.…”
Section: Resultsmentioning
confidence: 94%